Spatial distribution of exotic lumbricid earthworm Octolasion tyrtaeum in endangered Taxus contorta stands across Northwest Himalayan moist temperate forests - Diksha Negi; Shakoor Ahmed; J. M. Julka; Modhi O. Alotaibi; Kasahun Gudeta; Umesh Sharma; Sunny Sharma (Scientific Reports)
Abstract This study investigates the distribution and ecological implications of earthworm populations in a moist temperate forest of the northwest Himalayas, located in Himri within the Sunni Forest Division of District Shimla, Himachal Pradesh. Over a two-year period, a total of 1101 earthworms were collected during the autumn and spring seasons from the understory of Taxus contorta Griff., an endangered conifer species listed by the IUCN. All specimens were identified as Octolasion tyrtaeum (Savigny), an exotic lumbricid earthworm of European origin. The distribution of O. tyrtaeum showed significant variation in mean density and biomass across north-, northeast-, and southwest-facing slopes. Principal Component Analysis revealed that litter thickness, soil moisture, and organic carbon content were the primary environmental variables influencing earthworm distribution. Pearson correlation analysis further supported significant positive relationships between earthworm abundance and factors such as soil moisture, organic carbon, canopy cover, and litter depth, while negative correlations were observed with pH, electrical conductivity, and temperature. Invasive earthworms like O. tyrtaeum can significantly affect ecosystems by altering plant diversity, soil properties, and nutrient cycling. The moist temperate forests of the Northwest Himalayas are increasingly vulnerable to climate change and anthropogenic disturbances, including deforestation and land-use changes. These stressors, combined with the spread of invasive O. tyrtaeum, pose a growing threat to native biodiversity and ecosystem stability. The findings underscore the urgent need for targeted monitoring and conservation strategies to mitigate the ecological impacts of exotic earthworms in fragile Himalayan Forest ecosystems.